Comparative analysis of passive defences in spiders (Araneae) - Pekár, Stano (The Journal of animal ecology, 2014)
Being frequent prey of many predators, including especially wasps and birds, spiders have evolved a variety of defence mechanisms. Here I studied patterns of passive defences, namely anachoresis, crypsis, masquerade, aposematism and Batesian mimicry, in spiders. Using published information pertaining more than 1000 spider species, the phylogenetic pattern of different passive defences (i.e. defences that decrease the risk of an encounter with the predator) was investigated. Furthermore, I studied the effect of foraging guild, geographical distribution and diel activity on the frequency of defences as these determine the predators diversity, presence and perception. I found that crypsis (background matching) combined with anachoresis (hiding) was the most frequent defence confined mainly to families/genera at the base of the tree. Aposematism (warning coloration) and Batesian mimicry (imitation of noxious/dangerous model) were found in taxa that branched later in the tree, and masquerade (imitation of inedible objects) was confined to families at intermediate positions of the tree. Aposematism and Batesian mimicry were restricted to a few lineages. Masquerade was used particularly by web-building species with nocturnal activity. Aposematism was rare but mainly used by web-building diurnal species. Batesian mimicry was frequently observed in cursorial species with diurnal activity. Cryptic species were more common in temperate zones, whereas aposematic and mimetic species were more common in the tropics. Here I show that the evolution of passive defences in spiders was influenced by the ecology of species. Then, I discuss the evolutionary significance of the particularly defences.
Keywords: pavouci; Predatory Behavior; cirkadiánní rytmus; chování zvířat; Phylogeny; Food Chain; predátorské chování; aposematism; evolution; rozšíření zvířat; Biological Mimicry; Animal Distribution; zvířata; masquerade; crypsis; Circadian Rhythm; mimikry; mimicry; fylogeneze; Spiders; anachoresis; Animals; Behavior, Animal; potravní řetězec